Another new species of Cyrtodactylus Gray, 1927 (Squamata: Gekkonidae) of the angularis group from the karstic landscape of Phong Nha-Ke Bang National Park, central Vietnam - Duong, Tang Van; Vu, Lien Van; Vu, Hien Thi Thu; Mulcahy, Dan; Bragin, Andrey M.; Jr., Nikolay A. Poyarkov; Grismer, L. Lee (Zootaxa, 2024)
The Phong Nha-Ke Bang (PNKB National Park in the Central Highlands of Vietnam is a bastion for the protection and conservation of Vietnam’s natural heritage. Thus, the discovery of yet another new species of Cyrtodactylus, C. hangvaensis sp. nov., within the PNKB continues to underscore the parks ever-growing importance. Cyrtodactylus hangvaensis sp. nov. is a karst dwelling species of the angularis group that based on a molecular phylogenetic analysis, is most closely related to C. roesleri from the PNKB and C. sommerladi from karstic areas in nearby Laos. Cyrtodactylus hangvaensis sp. nov. occupies a unique position in morphospace where it is well separated from closely related species and other species within the PNKB. It is potentially diagnosable from all other members of the angularis by having a unique combination of morphological and color pattern characters and bearing an uncorrected pairwise sequence divergence of 9.5%–25.5%.